Chemistry of bone remodelling preserved in extant and fossil Sirenia. Issue 5 (29th February 2016) - Anné, Jennifer; Wogelius, Roy A.; Edwards, Nicholas P.; van Veelen, Arjen; Ignatyev, Konstantin; Manning, Phillip L.
Abstract : Bone remodelling is a crucial biological process needed to maintain elemental homeostasis. Abstract : Bone remodelling is a crucial biological process needed to maintain elemental homeostasis. It is important to understand the trace elemental inventories that govern these processes as malfunctions in bone remodelling can have devastating effects on an organism. In this study, we use a combination of X-ray techniques to map, quantify, and characterise the coordination chemistry of trace elements within the highly remodelled bone tissues of extant and extinct Sirenia (manatees and dugongs). The dense bone structure and unique body chemistry of sirenians represent ideal tissues for studying both high remodelling rates as well as unique fossilisation pathways. Here, elemental maps revealed uncorrelated patterning of Ca and Zn within secondary osteons in both extant and fossil sirenians, as well as elevated Sr within the connecting canals of fossil sirenians. Concentrations of these elements are comparable between extant and fossil material indicating geochemical processing of the fossil bone has been minimal. Zn was found to be bound in the same coordination within the apatite structure in both extant and fossil bone. Accurate quantification of trace elements in extant material was only possible when the organic constituents of the bone were included. The comparable distributions, concentrations, and chemical coordination of these physiologically important trace elements indicate the chemistry of bone remodelling has been preserved for 19 million years. This study signifies the powerful potential of merging histological and chemical techniques in the understanding of physiological processes in both extant and extinct vertebrates.